The Increase of the Capacity of the Regional Income in Receiving the Regional Original Income in Supiori District - Hasim, Djamil; Handayani, Sri; Rumere, Onesias (Universitas Negeri Makassar, 2021)
Â Regional revenue agencies in organizing local tax revenues and regional levies have not been maximized because there are several problems faced in increasing their capacity, namely the problem of limited human resources. Therefore, this study aims to determine the strategy of increasing the capacity of the Regional Revenue Agency for the framework of local tax and levy receipts in increasing Regional Original Income and what factors determine the efforts to increase the capacity of the Regional Revenue Agency to increase taxes and levies in receiving Regional Original Income. This study uses a descriptive research method with a qualitative approach. The results of the study indicate that the increase in the capacity of the Regional Revenue Agency Building in receiving Regional Original Revenue is associated with the quality of the Human Resources apparatus, so it has not been balanced with the competence of the relevant apparatus' ability to carry out their duties and functions properly and several factors were detected as determining factors in the improvement process. the capacity of apparatus resources to increase the capacity of local taxes and levies in Supiori Regency. These determining factors include the ability of the implementers in the areas of revenue planning, data processing and finance as well as collection. Another determining factor is the problem of facilities and facilities as well as problems related to the division of tasks and functions of the existing sections. This is one with other factors that have their respective roles that are interrelated so that they have an impact on increasing local tax revenues and levies during 2012-2017 in Supiori Regency.